IMPROVING THE PERFORMANCE OF TESTING LABORATORY EMPLOYEES OF XYZ CENTER BASED ON THEIR RELATIONSHIP WITH MENTAL WORKLOAD - Za’imah, Fina (PEOPLE: International Journal of Social Sciences, 2024)
Balai XYZ is one of the government agencies engaged in services, one of which is material testing. Based on performance value data, about 30% of technicians have less good value. The suspected factor is the pressure in work so that the mental workload increases. Therefore, it is necessary to measure the mental workload using Subjective Workload Dominance method. The measurement results show that many technicians have a heavy mental workload, especially on D and F. In addition, there is a significant negative relationship between workload and performance value. Proposed performance improvements include SOP improvements for D and F assignments, rejuvenation of test kits and assistive devices, as well as improvements to machine tool work instructions.